Alcohol Misuse Among Female Veterans: Exploring Associations With Interpersonal Violence and Mental Health. (6th December 2015) - Gobin, Robyn L.; Green, Kelly E.; Iverson, Katherine M.
Abstract : Background : The correlates of alcohol misuse among female Veterans are not well understood. The present study explored associations among alcohol misuse, demographic/military-related characteristics, interpersonal violence exposure, and posttraumatic stress disorder (PTSD) and depression symptom severity. Method : Participants were 369 female Veteran patients of the VA New England Healthcare System. Participants completed a paper-and-pencil mail survey that included validated assessments of alcohol misuse, interpersonal violence, and psychological distress. Results : Younger age, adulthood physical abuse, military sexual trauma, past-year psychological aggression by an intimate partner, and PTSD and depression symptom severity showed significant univariate associations with alcohol misuse (as indicated by unsafe drinking levels, presence or incipience of an alcohol use disorder, intrapersonal alcohol-related concerns, and/or interpersonal alcohol-related concerns). A couple of these associations remained significant when examined in logistic regression models. Conclusions : Findings suggest that female Veterans who are at risk for alcohol use disorders and/or are experiencing alcohol-related problems may benefit from screening and intervention efforts that take into account interpersonal violence exposures and mental health symptoms on a case-by-case basis. Results also suggest the importance of future research examining correlates and risk factors for substance misuse among female Veterans.